Towards a Corpus-Based Analysis of Anglicisms in Spanish: A Case Study - Oncins-Martínez, José L. (International Journal of English Studies, 2009)
This paper aims to show some of the advantages of and the need for using corpora for exploring and assessing Anglicisms in contemporary Spanish. In order to do this a case study is presented: the adverb dramáticamente, as it is taking on the new sense ‘espectacularmente’ under the influence of English dramatically. The presence of this adverb with this new sense in contemporary Spanish is explored and supported with the data found in CORDE and CREA, the two corpora of the Royal Spanish Academy. Since the paper also seeks to show in what ways the Spanish lexicon is being influenced by English, evidence from two major English corpora, the BNC and the COCA, will be used.